Impact of the line of treatment on progression-free survival in patients treated with T-DM1 for metastatic breast cancer - A. Migeotte (BMC, 2021)
Abstract Background Trastuzumab emtansine (T-DM1) is indicated as second-line treatment for human epidermal growth factor receptor 2 (HER2)-positive metastatic or unresectable locally advanced breast cancer, after progression on trastuzumab and a taxane-based chemotherapy. We wished to determine if the line of treatment in which T-DM1 is administered has an impact on progression-free survival (PFS) and in particular, if prior treatment with capecitabine/lapatinib or pertuzumab modifies PFS of further treatment with T-DM1. Patients and methods We performed a multicenter retrospective study in 3 Belgian institutions. We evaluated PFS with T-DM1 in patients treated for HER2 positive metastatic or locally advanced unresectable breast cancer between January 1, 2009 and December 31, 2016. Results We included 51 patients. The median PFS was 9.01 months. The line of treatment in which T-DM1 (1st line, 2nd line, 3rd line or 4+ lines) was administered had no influence on PFS (hazard ratio 0.979, CI95: 0.835–1.143). There was no significant difference in PFS whether or not patients had received prior treatment with capecitabine/lapatinib (9.17 vs 5.56 months, p-value 0.875). But, patients who received pertuzumab before T-DM1 tended to exhibit a shorter PFS (3.55 months for T-DM1 after pertuzumab vs 9.50 months for T-DM1 without pretreatment with pertuzumab), even if this difference was not statistically significant (p-value 0.144). Conclusion Unlike with conventional chemotherapy, the line of treatment in which T-DM1 is administered does not influence PFS in our cohort of patients with advanced HER2-positive breast cancer.